Efektivitas Penggunaan Media Pembelajaran POSFIVA dalam Meningkatkan Minat Belajar dan Hasil Belajar Siswa - Rahmawati, Farida (Jurnal Pendidikan Madrasah, 2023)
This research is a pre-experimental study, which aims to determine the application of POSFIVA learning media to improve student interest and learning outcomes. This study used The Static Group Comparison Design model method by forming one group for experiments and one control group. The results showed data on student learning interest in the use of POSFIVA learning media amounted to 66.53% of students gave a very positive response and 33.47 students gave a positive response, with an average score of 89.88. Student learning interest in the use of POSFIVA learning media includes several indicators, namely: (1) interest, (2) pleasure, (3) attention, (4) participation, (5) curiosity. The use of POSFIVA learning media can increase student interest and learning outcomes.